Pengaruh Jenis Media Tanam dan Konsentrasi Nutrisi AB Mix Terhadap Tinggi Tanaman, Jumlah Daun dan Berat Basah Tajuk Tanaman Pakcoy (Brassica rapa L.) Secara Hidroponik - Rizky Wahyu Lestari; Nova Triani; Makhziah (Universitas Islam Raden Rahmat, Malang, 2024)
Pakcoy plants have good potential to be cultivated. Land conversion causes a reduction in productive land so hydroponics is a solution to the problem. The purpose of this study was to determine the effect of planting media types (firewood husk, cocopeat and rockwool) and AB Mix nutrient concentrations (1.000 ppm, 1.200 ppm and 1.400 ppm) on the growth and yield of pakcoy plants in hydroponic wick systems. This research was conducted in Mojokerto City using the Randomized Group Design method with 3 replications. The results of the treatment given that the type of planting media and AB Mix nutrient concentration, the treatment of cocopeat planting media type and AB Mix nutrient concentration of 1.200 ppm had an effect on plant height, number of leaves and fresh weight of pakcoy plant crowns.